Research tools for studying modern trends in the implementation of ESG practices in Russian companies - I. N. Tkachenko; L. A. Ramenskaya (Модернизация, инновация, развитие)
Purpose: is to test the research tools for studying modern trends in the implementation of ESG practices and their effectiveness in Russian companies.   Methods: this article examines the applicability of the research tools for analyzing the activities of organizations in the direction of the ESG agenda. We analyzed such tools as comparative analysis of fi nancing ESG projects, content analysis of report texts, regression analysis of the relationship between the ESG ratings and the fi nancial performance of the company. A comparative analysis of methods was carried out based on the results of appropriation of instruments.   Results: the main result of the reporting analysis is the identifi cation of a trend towards reducing disclosure of information on the financing of ESG projects. We can identify main areas of investment in requests from external and internal stakeholders based on available financing information. The conclusion about the increase in mentions of social projects and initiatives in the fi eld of environmental protection based on a content analysis results. We also identifi ed the highest priority areas for each of the ESG components. The main priorities are: the social agenda – "employee welfare"; responsible attitude to the environment – "reduction of greenhouse gas emissions", "energy–efficient materials and technologies", "waste management" and "water consumption"; corporate governance – "observance of shareholders' rights". The hypothesis about the positive impact of ESG rating on company value confi rmed. There was a positive relationship between a company's environmental performance and value, as well as a negative relationship between value and social performance.   Conclusions and Relevance: despite the challenges and sanctions restrictions, Russian companies continue to be active in the ESG field. For a more complete analysis of the ESG projects and their coverage in non-financial reporting, it is preferable to use a combination of research tools.